Bacterial colonization, species diversity and antimicrobial susceptibility patterns of indwelling urinary catheters from postpartum mothers attending a Tertiary Hospital in Eastern Uganda - Nakawuki, Ashley Winfred; Nekaka, Rebecca; Ssenyonga, Lydia V. N.; Masifa, George; Nuwasiima, Dorreck; Nteziyaremye, Julius; Iramiot, Jacob Stanley (PLoS ONE, 2022)
Postpartum urinary Catheter-Related Infections (CRIs) are a significant cause of maternal sepsis. Several studies done have reported the presence of mixed populations of bacteria with a significant increase in Extended-Spectrum Beta-Lactamase (ESBL) Enterobacteriaceae spps, Methicillin-Resistant Staphylococcus aureus (MRSA), Multi-Drug Resistant (MDR) bacteria in urine and blood cultures of catheterized patients despite the use of prophylactic antibiotics. This study aimed at determining the bacterial species diversity and susceptibility patterns of indwelling urinary catheters from postpartum mothers attending Mbale Regional Referral Hospital (MRRH). Methods A cross-sectional study employing quantitative and qualitative was carried out in MRRH among postpartum mothers with urinary catheters and their care-takers. The purposive non-random sampling strategy was used to collect data using an interviewer-administered questionnaire for the quantitative data collection and in-depth interviews for qualitative data collection. All the data collection tools used were developed, pretested and validated. At the point of de-catheterization, Catheter tips from enrolled participants were cut about 2-3cm below the balloon aseptically into test-tube containing peptone water, sonication technique employed, and incubation done 24hours then cultured to ensure phenotypic identification. An antibiotic sensitivity test was performed using the disc diffusion method following Clinical and Laboratory Standards Institute (CLSI) guidelines. Quantitative data collected was entered in Microsoft Excel and then exported to STATA14 for statistical analysis. Thematic analysis was used to analyse and organise qualitative data by an inductive coding method using Nvivo 12 software. Results In this study, 208 postpartum mothers participated, the majority of whom were caesarean section mothers of age range 20–24 years and 17 care-takers with a median age of 32 years. The prevalence of catheter tips bacterial colonisation was 98% despite 88.5% of the participants being on broad-spectrum antibiotics. The average duration of catheterisation was 2 days. All bacteria isolates were potential uro-pathogens with a mean occurrence of 2 bacteria species in each urinary catheter tip. The rates of MDR to commonly used antibiotics were high. The urinary catheter size of greater than F14 and duration of catheterization greater than 2 days were significantly associated with the number of bacterial species isolated from each sample. The maintenance care and knowledge of care-urinary catheter care among the care-takers was found sub-optimal. Conclusion There was a high prevalence of catheter colonisation with bacterial spps diversity averaging 2 spps per sample despite use of broad spectrum antibiotics. The MDR rates were high, which calls for routine culture and sensitivity. Health workers practicing obstetric medicine need to pay attention to catheter sizes during catheterisation and its duration. Health education should be part of antenatal and postnatal care education.
Keywords: Bacterial colonization; Species diversity; Antimicrobial susceptibility; Urinary catheters